Performance Assessment of Sri Lankan Prehospital Ambulance Service - Pamila Sadeeka ADIKAR; Ravindra PATHIRATHNA, Dr; Chanaka LIYANAGE, Dr; Pradeep RATNASEKARE, Dr (Albanian Journal of Trauma and Emergency Surgery, 2020)
Background: Ischemic Heart Disease (IHD) is the leading cause of mortality that raised demand for pre-hospital emergency care in Sri Lanka. Understanding the performance of Sri Lanka's 1990 ambulance service is essential to improve its quality and to reduce morbidity and mortality associated with the disease. This study aims to describe socio-demographic characteristics, evaluate the clinical assessment and management process of patients presenting with acute chest pain of cardiac in origin.